The Jesus People : attitude, personal-orientation and life-style changes as a function of non-conformist religious influence - Stones, Christopher R (Rhodes University, Faculty of Humanities, Department of Psychology, 1976)
The Jesus People of Hillbrow, Johannesburg, assert that since joining the Jesus movement they have undergone radical changes; from a life of turmoil to a life of relative serenity. Such claims, if valid, have implications for the counter-culture, which is comprised largely of youth alienated from mainstream society and church. The present study then, was an investigation to determine whether the members of the Jesus movement have changed and if so, attempts were made to delineate such changes. The Jesus People investigated were members of the "Invisible Church", who had been residing communally for a period of not less than three months. A battery of questionnaires was administered on two occasions. The first occasion required the subjects to complete the questionnaires as they would have prior to their conversion, while the second administration required that the subjects complete the questionnaires according to their attitudes, values and opinions presently held. To counter any practice effects, the requirements for completion of the questionnaires were reversed for one half of the group randomly chosen. The order of presentation of the questionnaires was kept the same to counter any fatigue-effects. (The control group being matched with the experimental group should experience the same degree of fatigue.) The individuals selected for the control group were recruited from established-church youth clubs. These individuals were matched with the members of the Jesus movement for age, sex, home-language, general intelligence and occupation of father. The procedure of questionnaire administration for the control group was identical to that adopted for the experimental group. Both the experimental and the control group comprised 22 individuals. Incidental to the major design of the present study was the generation of a small (eight) group of Pentecostals, the results of which were analysed separately from those of the experimental and control groups. The finding that this group underwent the least change did not support the a priori expectation that Pentecostals should show changes which are intermediate to those of the experimental and control groups. It is argued however, that this Pentecostal group is not representative of Pentecostals per se. Bearing in mind, that the answers received depend, to a large extent, on the nature of the questions posed, the Jesus People, as a function of conversion (operationally defined as a "Jesus Experience"), underwent significant increases in their degree of perceived security but revealed significant decreases on attributes related to self-actualization. In addition, their predominant life-style orientation changed from personalistic to sociocentric, and there was an increased support for biblicistic fundamentalism. Associated with the above changes were decreases on the majority of the Wilson conservatism-scale dimensions, together with changes on a questionnaire explicitly developed for the present study. It is argued that the changes undergone by the members of the Jesus movement are in a positive direction, the "Invisible Church" serving as a 'half-way house'. Such changes are posited to be a function of an operationally defined "Jesus Experience"; a psycho-sociological experience rather than a theological, ecclesiastical experience.
Keywords: Jesus People -- South Africa -- Johannesburg -- Hillbrow -- Attitudes; Youth -- South Africa -- Johannesburg -- Hillbrow -- Religious life; Religious communities -- South Africa